(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2017)
Hinduism and Buddhism in the Nusantara between the 7th and 14th centuries had a significant influence on the Malay world. It changed the values and the worldview of the Malays who practised animism and ancestral religions. This study analyses the symbolism of devar?ja (god-king) as manifest in the cult practised by the people in Southeast Asia and that has a significant influence on Malay literature. The data was collected from primary sources such as “Hikayat Banjar”, “Hikayat Parang Puting”, “Hikayat Sang Boma”, “Hikayat Panji Semirang” and “Hikayat Malim Deman”. The sample is considered neutral due to the different literary genres comprising pre-Islamic texts, anecdotes, history, and the literature produced during the religio-transitional period. The sample is limited to five texts. The result of this study will demonstrate the different styles of writing that used the symbolism of devar?ja to emphasise the sovereignty of the Malay rulers. Agama Hindu-Buddha yang berkembang dari abad ke-7 sehingga abad ke-14 Masihi di Nusantara memberi pengaruh yang besar terhadap dunia Melayu. Kemasukan pengaruh kebudayaan Hindu-Buddha mengubah nilai-nilai kebudayaan dan pandangan semesta orang Melayu di Nusantara yang sebelumnya mengamalkan animisme serta agama nenek moyang. Makalah ini menganalisis simbolisme dewa-raja yang dijadikan kultus dalam masyarakat di Asia Tenggara yang turut tercermin dalam karya kesusasteraan Melayu klasik. Pengumpulan data dibuat menggunakan sumber primer seperti Hikayat Banjar, Hikayat Parang Puting, Hikayat Sang Boma, Hikayat Panji Semirang dan Hikayat Malim Deman. Pemilihan sampel kajian ini adalah neutral kerana dipilih mengikut genre yang berbeza, iaitu sastera pra-Islam, anekdot, sastera sejarah dan sastera zaman transisi Hindu-Islam. Bahan kajian terbatas kepada lima teks sastera Melayu klasik. Hasil kajian memperlihatkan kepelbagaian cara kepengarangan digunakan bagi menonjolkan simbolisme dewa-raja dalam menyerlahkan kedaulatan raja-raja Melayu.